Asthma and COPD : basic mechanisms and clinical management - Barnes, Peter J., 1946-; ClinicalKey eBooks (Amsterdam ; Boston : Elsevier/Academic Press, 2009)
The Second Edition of Asthma and COPD: Basic Mechanisms and Clinical Management continues to provide a unique and authoritative comparison of asthma and COPD. Written and edited by the world's leading experts, it continues to be a comprehensive review of the most recent understanding of the basic mechanisms of both conditions, specifically comparing their etiology, pathogenesis, and treatments. Each chapter considers Asthma and COPD in side-by-side contrast and comparison - not in isolation - in the context of mechanism, triggers, assessments, therapies, and clinical management. Presents the latest and most comprehensive understandings of the mechanisms of inflammation in both Asthma and COPD. Most extensive reference to primary literature on both Asthma and COPD in one source. Easy-to-read summaries of the latest advances alongside clear illustrations.
1Definitions, Epidemiology and Genetics of Asthma and COPD -- 2Epidemiology -- 3Natural History -- 4Genetics of Asthma and COPD -- 5Pulmonary Physiology -- 6Airway Pathology -- 7Airway Remodeling -- 8Animal Models -- 9Mast Cells and Basophils -- 10Dentritic Cells -- 11Macrophages -- 12Eosinophils -- 13Lymphocytes -- 14Neutrophils -- 15Fibroblasts -- 16Epithelial Cells -- 17Mucus and Mucin-Secreting Cells -- 18Airway Smooth Muscle -- 19Tracheobronchial Circulation -- 20Pulmonary Vessels -- 21Adhesion Molecules -- 22Extracellular Matrix -- 23Prostanoids -- 24Leukotrienes and Lipoxins -- 25Reactive Oxygen Species -- 26Chemokines -- 27Cytokines -- 28Matrix Degrading Proteinases -- 29Growth Factors, -- 30Nitric Oxide -- 31Transcription Factors -- 32Neural and Humoral Control -- 33Pathophysiology of Asthma -- 34Pathogenesis of COPD -- 35Allergens -- 36Occupational Agents -- 37Infections -- 38Exercise as a Stimulus -- 39Atmospheric Pollutants -- 40Drugs -- 41Diagnosis -- 42Non-invasive Assessment of Airway Inflammation -- 43Imaging -- 44Systemic Manifestations -- 45 Cardiovascular Effects -- 46Allergen Avoidance -- 47Smoking Cessation -- 48́2-adrenoceptor Agonists -- 49Anticholinergic Bronchodilators -- 50Theophylline -- 51Corticosteroids -- 52Mediator Antagonists -- 53Antibiotics -- 54Long-term Oxygen Therapy -- 55Immunomodulators -- 56Pulmonary Vasodilators -- 57Ventilator Support -- 58Pulmonary Rehabilitation -- 59Surgery and Other Mechanical Interventions -- 60Other Therapies -- 61Future Therapies -- 62Health Economics -- 63Management of Chronic Asthma in Adults -- 64Asthma Exacerbations -- 65Childhood Asthma -- 66Treatment for Stable COPD -- 67Acute Exacerbations of COPD -- 68Education and Self-Management.
Includes bibliographical references and index.
Print version record.
Elsevier
Elsevier
Keywords: Asthma; Asthma -- Treatment; Lungs -- Diseases, Obstructive; Lungs -- Diseases, Obstructive -- Treatment; MEDICAL -- Pulmonary & Thoracic Medicine; HEALTH & FITNESS -- Diseases -- Respiratory; Asthma; Asthma -- Treatment; Lungs -- Diseases, Obstructive; Lungs -- Diseases, Obstructive -- Treatment; Asthma -- pathology; Asthma -- therapy; Pulmonary Disease, Chronic Obstructive -- pathology; Pulmonary Disease, Chronic Obstructive -- therapy; Electronic books